Approaching a closer surrogate for the biologically effective dose with subcellular partitioning-based toxicokinetic models. Issue 10 (19th May 2023) - Le, T. T. Yen; Geffard, Olivier; Geffard, Alain; Peijnenburg, Willie J. G. M.
Abstract: A general concept in risk assessment is that a threshold of exposure exists above which adverse effects are initiated. Toxicity is related to the target-site concentration or the biologically active dose. Although it is often a huge challenge to measure the specific dose metric of metal toxicity, significant progress has been obtained to approach closer to the target-site concentration. Such developments are reviewed in the present study. In addition, a general framework to simulate the subcellular metal partitioning, which is supposed to account for the internal metal sequestration, is developed and applied to various metals. The framework allows for delineating mechanisms of internal metal sequestration. Moreover, the specificity in these mechanisms, which varies among metals, species, and exposure conditions, might explain the complicated relationship between the internal concentration and metal toxicity. Attention should be paid to the data requirements as the high number of unknown parameters might be accompanied by potential uncertainties. In addition, future efforts should focus on linking the concentration of metals in sensitive fractions and toxicological effects. Graphical abstract: UF0001